Discovery Learning Learning Analysis to Develop High Level Cognitive Learning Outcomes Based on Student Metacognitive Characteristics - Rahayu, Putri; Yulianti, Dwi; Adha, Muhammad Mona; Perdana, Ryzal; Nurwahidin, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
Study findings about students' learning needs became the basis for this research. To improve high-level cognitive learning outcomes based on students' metacognitive characteristics, this research will apply Discovery Learning. This research uses Solomon Four Groups Design, a type of quasi-experimental research methodology. The research population was 216 fourth grade students at Al Kautsar Elementary School. In keeping with the research objectives, a cluster random sampling approach was used to select the sample for this investigation, resulting in a total of 112 students. The data analysis method uses the Man Whitney test which is non-parametric. Research findings show that discovery learning is effectively implemented in elementary schools because it can foster student participation in learning activities, which in turn can improve cognitive learning outcomes at a high level based on students' metacognitive characteristics.